High-breathability fabric and preparation method thereof

Through the esterification reaction and cross-linking network of modified cellulose and graphene oxide, combined with the coordination structure of silver nitrate, the problem of cotton fibers being easily adsorbed microorganisms is solved, and the long-lasting antibacterial properties and mechanical properties of high breathable fabrics are improved. , a high breathable fabric with excellent hygroscopicity and anti-aging properties are formed.

CN119145072AInactive Publication Date: 2024-12-17NANTONG JIAYUSI TEXTILE GROUP
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411621836.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Cotton fibers are prone to adsorbing microorganisms and lead to odor and mold, and traditional antibacterial technology is mainly in the field of chemical fibers, and lacks natural fiber antibacterial products, which affects health and the environment.

Method used

Modified cellulose, modified graphene oxide, hydrogen-containing silicone oil, polyethylene glycol and silver nitrate were mixed and spinned and weaved. Carbon-carbon double bonds and carboxy groups were introduced through the esterification reaction to form a stable coordination structure. Improve antibacterial and breathable properties, and use cross-linking networks to improve mechanical properties.

Benefits of technology

It realizes the long-lasting antibacterial, hygroscopic and anti-aging properties of highly breathable fabrics, enhances the mechanical properties and breathability of the fabrics, and solves the problem that cotton fibers are prone to adsorbing microorganisms.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_6
    Figure SMS_6
  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
Patent Text Reader

Abstract

The invention discloses a high-breathability fabric and a preparation method thereof, and relates to the field of fabrics. When the high-breathability fabric is prepared, cotton cellulose sequentially reacts with allyl succinic anhydride and 4 '-amino-2, 2': 6 ', 2'-terpyridyl to obtain modified cellulose; the preparation method comprises the following steps: sequentially reacting graphene oxide with thionyl chloride, 2, 4-diamino-6-vinyl-S-triazine and 2, 6-di-tert-butyl-4-bromomethylphenol, so as to obtain modified graphene oxide; uniformly mixing the modified cellulose, the modified graphene oxide, hydrogen-containing silicone oil, polyethylene glycol and silver nitrate, and spinning and weaving to obtain the high-breathability fabric. The high-breathability fabric prepared by the invention has excellent moisture absorption and breathability, lasting antibacterial property, mechanical property and photo-oxidative aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fabrics, in particular to a highly breathable fabric and a preparation method thereof. Background Art

[0002] Textiles are closely related to people's lives. Clothing is a protective barrier for the human body. How to effectively prevent bacteria from harming human health has attracted close attention. In recent years, antibacterial textiles have been widely used in textiles, medicine, food and other fields, but traditional antibacterial technology is mainly used in the field of chemical fibers. In order to reduce dependence on petroleum resources and reduce our environmental pollution, natural fiber antibacterial products are urgently needed to be developed.

[0003] Cotton is one of the main raw materials in the textile industry. It is a natural and environmentally friendly natural cellulose source. It has many excellent characteristics, such as soft feel, good warmth retention, good moisture absorption and air permeability, good chemical stability, and easy processing. Therefore, it is widely used in people's underwear and medical dressings. However, cotton fiber is very easy to adsorb various microorganisms and is extremely easy to become a habitat for bacteria or fungi. When the conditions are more suitable, these microorganisms will multiply in large numbers, not only causing a series of problems such as stinking and mold in daily life, but also easily spreading diseases in crowded places, and easily causing serious consequences such as wound infection in medical treatment, which threatens people's health. Therefore, the antibacterial modification research of cotton fiber is particularly important. Compared with natural and organic antibacterial agents, inorganic (metal and metal oxide) antibacterial agents have the advantages of good heat resistance, broad antibacterial spectrum, long effective period, low cytotoxicity, no drug resistance, and high safety. Silver ions belong to a kind of metal-type inorganic antibacterial agent, with low toxicity and broad-spectrum antibacterial properties. Therefore, the present invention prepares a highly breathable fabric with excellent and lasting antibacterial properties. Summary of the invention

[0004] The object of the present invention is to provide a highly breathable fabric and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A highly breathable fabric is obtained by spinning and weaving after uniformly mixing modified cellulose, modified graphene oxide, hydrogen-containing silicone oil, polyethylene glycol and silver nitrate.

[0006] As an optimization, the hydrogen-containing silicone oil model is TSF484, which comes from Jining Tangyi Chemical Co., Ltd.

[0007] As an optimization, the polyethylene glycol model is PEG400, which comes from Xingtai Xinlanxing Technology Co., Ltd.

[0008] As an optimization, the modified cellulose is obtained by sequentially reacting cotton cellulose with allyl succinic anhydride and 4'-amino-2,2':6',2''-terpyridine.

[0009] As an optimization, the cotton cellulose comes from Zhengzhou Huajing Chemical Co., Ltd.

[0010] As an optimization, the modified graphene oxide is obtained by reacting graphene oxide with thionyl chloride, 2,4-diamino-6-vinyl-S-triazine, and 2,6-di-tert-butyl-4-bromomethylphenol in sequence.

[0011] As an optimization, the graphene oxide model is LG-1402, which comes from Henan Wanying Refractory Materials Technology Co., Ltd.

[0012] A method for preparing a highly breathable fabric comprises the following steps: (1) Cotton cellulose, urea and choline chloride were mixed in a mass ratio of 1:(24-26):(24-26), stirred at 75-85°C and 200-300 rpm for 4-6 min, allyl succinic anhydride was added in an amount of 2-4 times the mass of cellulose, cooled to 55-65°C and stirred for 5-15 min, anhydrous ethanol was added in an amount of 13-15 times the mass of cellulose, allowed to stand until the mass of the precipitate did not increase, and then centrifuged, washed with anhydrous ethanol for 3-5 times, and dialyzed in deionized water for 71-10 min using a 900-1100 Da dialysis membrane. 73h, freeze-dried to obtain pre-modified cellulose; the pre-modified cellulose and deionized water were mixed at a mass ratio of 1:(900-1100), ultrasonically dispersed for 10-20min, 4'-amino-2,2':6',2''-terpyridine in an amount of 2-3 times the mass of the pre-modified cellulose was added, stirred at 55-65℃ and 350-450r / min for 3-5h, cooled naturally to room temperature and then centrifuged, washed with deionized water and anhydrous ethanol for 3-5 times respectively, dried at 65-75℃ for 8-10h to obtain modified cellulose; (2) Graphene oxide, thionyl chloride, N,N-dimethylformamide and anhydrous acetonitrile were mixed in a mass ratio of 1:(11-12):(0.9-1.1):(900-1100), stirred at 55-65°C and 100-200 rpm for 4-6 hours, and 2,4-diamino-6-vinyl-S-triazine (16-17 times the mass of graphene oxide) was added. The mixture was stirred for another 4-6 hours and then centrifuged. The mixture was washed with deionized water for 3-5 times and freeze-dried. , obtaining pre-modified graphene oxide; mixing the pre-modified graphene oxide, 2,6-di-tert-butyl-4-bromomethylphenol, triethylamine and dichloromethane in a mass ratio of 1:(2-3):(0.01-0.02):(13-14), stirring at -1-1°C and 200-300rpm for 55-65min, filtering, washing with ethyl acetate and deionized water for 3-5 times respectively, and drying at 55-65°C for 5-7h to obtain modified graphene oxide; (3) Modified cellulose, modified graphene oxide, hydrogenated silicone oil, polyethylene glycol, dichloromethane and dimethyl sulfoxide are mixed in a mass ratio of 1:(0.02-0.04):(0.4-0.6):(0.01-0.02):(2.2-2.3):(6.7-6.8), and stirred at 20-30°C and 100-200 rpm for 20-30 min. Chloroplatinic acid (0.01-0.02 times the mass of the modified cellulose) and silver nitrate (0.02-0.04 times the mass of the modified cellulose) are added, and stirring is continued for 5-15 min to obtain a spinning solution. The spinning solution is subjected to electrospinning. After spinning, the spinning solution is allowed to stand at 75-85°C for 10-12 h, washed with deionized water for 3-5 times, and dried at 60-70°C for 8-10 h to obtain a highly breathable fiber. The highly breathable fiber is spun and woven by a textile machine to obtain a highly breathable fabric.

[0013] As an optimization, the reaction equation of the pre-modified cellulose in step (1) is: .

[0014] As an optimization, the reaction equation for modifying the cellulose in step (1) is: .

[0015] As an optimization, the reaction equation of the pre-modified graphene oxide in step (2) is: .

[0016] As an optimization, the reaction equation for modifying graphene oxide in step (2) is: .

[0017] As an optimization, the reaction equation of the highly air-permeable fiber in step (3) is: .

[0018] As an optimization, the spinning conditions of the electrospinning in step (3) are: spinneret inner diameter 0.6 mm, spinning voltage 17 kV, receiving distance 17 cm, injection pump flow rate 6.8 μL / min.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the highly breathable fabric, the present invention sequentially reacts cotton cellulose with allyl succinic anhydride and 4'-amino-2,2':6',2''-terpyridine to obtain modified cellulose; sequentially reacts graphene oxide with thionyl chloride, 2,4-diamino-6-vinyl-S-triazine and 2,6-di-tert-butyl-4-bromomethylphenol to obtain modified graphene oxide; and uniformly mixes the modified cellulose, modified graphene oxide, hydrogen-containing silicone oil, polyethylene glycol and silver nitrate, and then spins and weaves to obtain the highly breathable fabric.

[0020] Firstly, cotton cellulose is reacted with allyl succinic anhydride and 4'-amino-2,2':6',2''-terpyridine in sequence to obtain modified cellulose; graphene oxide is reacted with thionyl chloride, 2,4-diamino-6-vinyl-S-triazine and 2,6-di-tert-butyl-4-bromomethylphenol in sequence to obtain modified graphene oxide; allyl succinic anhydride is grafted onto cotton cellulose through esterification reaction to introduce carbon-carbon double bonds and carboxyl groups, and then the carboxyl groups and amino groups react to form hydrophilic amide bonds while introducing terpyridine structures, complexing silver ions to form a stable coordination structure, thereby improving the hygroscopicity and long-lasting antibacterial properties of highly breathable fabrics; 2,4-diamino-6-vinyl-S-triazine and 2,6-di-tert-butyl-4-bromomethylphenol are grafted onto graphene oxide in sequence, and the synergistic effect of triazine ring and hindered phenol structure is utilized to absorb ultraviolet rays while capturing oxidative free radicals, thereby improving the anti-aging properties of highly breathable fabrics.

[0021] Secondly, modified cellulose, modified graphene oxide, hydrogen-containing silicone oil, polyethylene glycol and silver nitrate are mixed and spun to produce highly breathable fabrics; hydrogen-containing silicone oil is used to form a cross-linked network between modified cellulose and modified graphene oxide to improve the mechanical properties of the highly breathable fabrics; small molecular weight polyethylene glycol is used as a porogen to form a fine pore structure to improve the air permeability of the highly breathable fabrics; silver nitrate is added to the spinning solution to form a stable coordination structure with terpyridine to improve the long-lasting antibacterial properties of the highly breathable fabrics. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Example 1

[0023] A method for preparing a highly breathable fabric, the method comprising the following steps: (1) Cotton cellulose, urea and choline chloride were mixed in a mass ratio of 1:24:24, stirred at 75°C and 200 rpm for 6 min, allyl succinic anhydride twice the mass of cellulose was added, the temperature was lowered to 55°C and stirring was continued for 15 min, anhydrous ethanol 13 times the mass of cellulose was added, the precipitate was allowed to stand until the mass of the precipitate did not increase, then centrifuged, washed with anhydrous ethanol 3 times, dialyzed in deionized water with a 900Da dialysis membrane for 73 h, and freeze-dried to obtain pre-modified cellulose; pre-modified cellulose and deionized water were mixed in a mass ratio of 1:900, ultrasonically dispersed for 10 min, 4'-amino-2,2':6',2''-terpyridine twice the mass of the pre-modified cellulose was added, stirred at 55°C and 350 r / min for 5 h, naturally cooled to room temperature and then centrifuged, washed with deionized water and anhydrous ethanol 3 times respectively, and dried at 65°C for 10 h to obtain modified cellulose; (2) Graphene oxide, thionyl chloride, N,N-dimethylformamide and anhydrous acetonitrile were mixed in a mass ratio of 1:11:0.9:900, stirred at 55°C and 100 rpm for 6 h, 2,4-diamino-6-vinyl-S-triazine (16 times the mass of graphene oxide) was added, stirred for 6 h, centrifuged, washed with deionized water for 3 times, and freeze-dried to obtain pre-modified graphene oxide; pre-modified graphene oxide, 2,6-di-tert-butyl-4-bromomethylphenol, triethylamine and dichloromethane were mixed in a mass ratio of 1:2:0.01:13, stirred at -1°C and 200 rpm for 65 min, filtered, washed with ethyl acetate and deionized water for 3 times respectively, and dried at 55°C for 7 h to obtain modified graphene oxide; (3) Modified cellulose, modified graphene oxide, hydrogenated silicone oil, polyethylene glycol, dichloromethane and dimethyl sulfoxide were mixed in a mass ratio of 1:0.02:0.4:0.01:2.2:6.7, and stirred at 20°C and 100 rpm for 30 min. Chloroplatinic acid (0.01 times the mass of the modified cellulose) and silver nitrate (0.02 times the mass of the modified cellulose) were added, and stirring was continued for 15 min to obtain a spinning solution. The spinning solution was subjected to electrospinning. After spinning, it was allowed to stand at 75°C for 12 h, washed with deionized water for 3 times, and dried at 60°C for 10 h to obtain a highly breathable fiber. The highly breathable fiber was spun and woven by a textile machine to obtain a highly breathable fabric. Example 2

[0024] A method for preparing a highly breathable fabric, the method comprising the following steps: (1) Cotton cellulose, urea and choline chloride were mixed in a mass ratio of 1:25:25, stirred at 80°C and 250 rpm for 5 min, allyl succinic anhydride 3 times the mass of cellulose was added, cooled to 60°C and stirred for 10 min, anhydrous ethanol 14 times the mass of cellulose was added, allowed to stand until the mass of the precipitate did not increase, then centrifuged, washed with anhydrous ethanol 4 times, dialyzed in deionized water with a 1000Da dialysis membrane for 72 h, and freeze-dried to obtain pre-modified cellulose; pre-modified cellulose and deionized water were mixed in a mass ratio of 1:1000, ultrasonically dispersed for 15 min, 4'-amino-2,2':6',2''-terpyridine 2.5 times the mass of the pre-modified cellulose was added, stirred at 60°C and 400 r / min for 4 h, naturally cooled to room temperature and then centrifuged, washed with deionized water and anhydrous ethanol 4 times respectively, and dried at 70°C for 9 h to obtain modified cellulose; (2) Graphene oxide, thionyl chloride, N,N-dimethylformamide and anhydrous acetonitrile were mixed in a mass ratio of 1:11.5:1:1000, stirred at 60°C and 150 rpm for 5 h, 2,4-diamino-6-vinyl-S-triazine (16.5 times the mass of graphene oxide) was added, stirred for 5 h, centrifuged, washed with deionized water for 4 times, and freeze-dried to obtain pre-modified graphene oxide; pre-modified graphene oxide, 2,6-di-tert-butyl-4-bromomethylphenol, triethylamine and dichloromethane were mixed in a mass ratio of 1:2.5:0.015:12, stirred at 0°C and 250 rpm for 60 min, filtered, washed with ethyl acetate and deionized water for 4 times respectively, and dried at 60°C for 6 h to obtain modified graphene oxide; (3) Modified cellulose, modified graphene oxide, hydrogenated silicone oil, polyethylene glycol, dichloromethane and dimethyl sulfoxide were mixed in a mass ratio of 1:0.03:0.5:0.015:2.25:6.75, and stirred at 25°C and 150 rpm for 25 min. Chloroplatinic acid (0.015 times the mass of the modified cellulose) and silver nitrate (0.03 times the mass of the modified cellulose) were added, and stirring was continued for 10 min to obtain a spinning solution. The spinning solution was subjected to electrospinning. After the spinning was completed, it was allowed to stand at 80°C for 11 h, washed with deionized water 4 times, and dried at 65°C for 9 h to obtain a highly breathable fiber. The highly breathable fiber was spun and woven by a textile machine to obtain a highly breathable fabric. Example 3

[0025] A method for preparing a highly breathable fabric, the method comprising the following steps: (1) Cotton cellulose, urea and choline chloride were mixed in a mass ratio of 1:26:26, stirred at 85°C and 300 rpm for 4 min, allyl succinic anhydride 4 times the mass of cellulose was added, cooled to 65°C and stirred for 5 min, anhydrous ethanol 15 times the mass of cellulose was added, allowed to stand until the mass of the precipitate did not increase, then centrifuged, washed with anhydrous ethanol 5 times, dialyzed in deionized water with a 1100Da dialysis membrane for 71 h, and freeze-dried to obtain pre-modified cellulose; pre-modified cellulose and deionized water were mixed in a mass ratio of 1:1100, ultrasonically dispersed for 20 min, 4'-amino-2,2':6',2''-terpyridine 3 times the mass of the pre-modified cellulose was added, stirred at 65°C and 450 r / min for 3 h, naturally cooled to room temperature and then centrifuged, washed with deionized water and anhydrous ethanol 5 times respectively, and dried at 75°C for 8 h to obtain modified cellulose; (2) Graphene oxide, thionyl chloride, N,N-dimethylformamide and anhydrous acetonitrile were mixed in a mass ratio of 1:12:1.1:1100, stirred at 65°C and 200 rpm for 4 h, 2,4-diamino-6-vinyl-S-triazine (17 times the mass of graphene oxide) was added, stirred for 4 h, centrifuged, washed with deionized water for 5 times, and freeze-dried to obtain pre-modified graphene oxide; pre-modified graphene oxide, 2,6-di-tert-butyl-4-bromomethylphenol, triethylamine and dichloromethane were mixed in a mass ratio of 1:3:0.02:14, stirred at 1°C and 300 rpm for 55 min, filtered, washed with ethyl acetate and deionized water for 5 times respectively, and dried at 65°C for 5 h to obtain modified graphene oxide; (3) Modified cellulose, modified graphene oxide, hydrogenated silicone oil, polyethylene glycol, dichloromethane and dimethyl sulfoxide were mixed in a mass ratio of 1:0.04:0.6:0.02:2.3:6.8, and stirred at 30°C and 200 rpm for 20 min. Chloroplatinic acid (0.02 times the mass of the modified cellulose) and silver nitrate (0.04 times the mass of the modified cellulose) were added, and stirring was continued for 5 min to obtain a spinning solution. The spinning solution was subjected to electrospinning. After spinning, it was allowed to stand at 85°C for 10 h, washed with deionized water for 5 times, and dried at 70°C for 8 h to obtain a highly breathable fiber. The highly breathable fiber was spun and woven by a textile machine to obtain a highly breathable fabric.

[0026] Comparative Example 1 A method for preparing a highly breathable fabric, the method comprising the following steps: (1) Graphene oxide, thionyl chloride, N,N-dimethylformamide and anhydrous acetonitrile were mixed in a mass ratio of 1:11.5:1:1000, stirred at 60°C and 150 rpm for 5 h, 2,4-diamino-6-vinyl-S-triazine (16.5 times the mass of graphene oxide) was added, stirred for 5 h, centrifuged, washed with deionized water for 4 times, and freeze-dried to obtain pre-modified graphene oxide; pre-modified graphene oxide, 2,6-di-tert-butyl-4-bromomethylphenol, triethylamine and dichloromethane were mixed in a mass ratio of 1:2.5:0.015:12, stirred at 0°C and 250 rpm for 60 min, filtered, washed with ethyl acetate and deionized water for 4 times respectively, and dried at 60°C for 6 h to obtain modified graphene oxide; (2) Cotton cellulose, modified graphene oxide, hydrogenated silicone oil, polyethylene glycol, dichloromethane and dimethyl sulfoxide were mixed in a mass ratio of 1:0.03:0.5:0.015:2.25:6.75, and stirred at 25°C and 150 rpm for 25 min. Chloroplatinic acid (0.015 times the mass of the modified cellulose) and silver nitrate (0.03 times the mass of the modified cellulose) were added, and stirring was continued for 10 min to obtain a spinning solution. The spinning solution was subjected to electrospinning. After spinning, it was allowed to stand at 80°C for 11 h, washed with deionized water 4 times, and dried at 65°C for 9 h to obtain a highly breathable fiber. The highly breathable fiber was spun and woven by a textile machine to obtain a highly breathable fabric.

[0027] Comparative Example 2 A method for preparing a highly breathable fabric, the method comprising the following steps: (1) Cotton cellulose, urea and choline chloride were mixed in a mass ratio of 1:25:25, stirred at 80°C and 250 rpm for 5 min, allyl succinic anhydride 3 times the mass of cellulose was added, cooled to 60°C and stirred for 10 min, anhydrous ethanol 14 times the mass of cellulose was added, allowed to stand until the mass of the precipitate did not increase, then centrifuged, washed with anhydrous ethanol 4 times, dialyzed in deionized water with a 1000Da dialysis membrane for 72 h, and freeze-dried to obtain pre-modified cellulose; pre-modified cellulose and deionized water were mixed in a mass ratio of 1:1000, ultrasonically dispersed for 15 min, 4'-amino-2,2':6',2''-terpyridine 2.5 times the mass of the pre-modified cellulose was added, stirred at 60°C and 400 r / min for 4 h, naturally cooled to room temperature and then centrifuged, washed with deionized water and anhydrous ethanol 4 times respectively, and dried at 70°C for 9 h to obtain modified cellulose; (2) Modified cellulose, graphene oxide, hydrogenated silicone oil, polyethylene glycol, dichloromethane and dimethyl sulfoxide were mixed in a mass ratio of 1:0.03:0.5:0.015:2.25:6.75, and stirred at 25°C and 150 rpm for 25 min. Chloroplatinic acid (0.015 times the mass of the modified cellulose) and silver nitrate (0.03 times the mass of the modified cellulose) were added, and stirring was continued for 10 min to obtain a spinning solution. The spinning solution was subjected to electrospinning. After spinning, it was allowed to stand at 80°C for 11 h, washed with deionized water 4 times, and dried at 65°C for 9 h to obtain a highly breathable fiber. The highly breathable fiber was spun and woven by a textile machine to obtain a highly breathable fabric.

[0028] Comparative Example 3 A method for preparing a highly breathable fabric, the method comprising the following steps: (1) Cotton cellulose, urea and choline chloride were mixed in a mass ratio of 1:25:25, stirred at 80°C and 250 rpm for 5 min, allyl succinic anhydride 3 times the mass of cellulose was added, cooled to 60°C and stirred for 10 min, anhydrous ethanol 14 times the mass of cellulose was added, allowed to stand until the mass of the precipitate did not increase, then centrifuged, washed with anhydrous ethanol 4 times, dialyzed in deionized water with a 1000Da dialysis membrane for 72 h, and freeze-dried to obtain pre-modified cellulose; pre-modified cellulose and deionized water were mixed in a mass ratio of 1:1000, ultrasonically dispersed for 15 min, 4'-amino-2,2':6',2''-terpyridine 2.5 times the mass of the pre-modified cellulose was added, stirred at 60°C and 400 r / min for 4 h, naturally cooled to room temperature and then centrifuged, washed with deionized water and anhydrous ethanol 4 times respectively, and dried at 70°C for 9 h to obtain modified cellulose; (2) Graphene oxide, thionyl chloride, N,N-dimethylformamide and anhydrous acetonitrile were mixed in a mass ratio of 1:11.5:1:1000, stirred at 60°C and 150 rpm for 5 h, 2,4-diamino-6-vinyl-S-triazine (16.5 times the mass of graphene oxide) was added, stirred for 5 h, centrifuged, washed with deionized water for 4 times, and freeze-dried to obtain pre-modified graphene oxide; pre-modified graphene oxide, 2,6-di-tert-butyl-4-bromomethylphenol, triethylamine and dichloromethane were mixed in a mass ratio of 1:2.5:0.015:12, stirred at 0°C and 250 rpm for 60 min, filtered, washed with ethyl acetate and deionized water for 4 times respectively, and dried at 60°C for 6 h to obtain modified graphene oxide; (3) Modified cellulose, modified graphene oxide, hydrogenated silicone oil, polyethylene glycol, dichloromethane and dimethyl sulfoxide were mixed in a mass ratio of 1:0.03:0.5:0.015:2.25:6.75, stirred at 25°C and 150 rpm for 25 min, 0.015 times the mass of modified cellulose of chloroplatinic acid was added, and stirring was continued for 10 min to obtain a spinning solution; the spinning solution was subjected to electrospinning, and after spinning, it was allowed to stand at 80°C for 11 h, washed with deionized water 4 times, and dried at 65°C for 9 h to obtain a highly breathable fiber; the highly breathable fiber was spun and woven by a textile machine to obtain a highly breathable fabric.

[0029] Test Case 1. Moisture absorption and breathability Hygroscopicity test method: Take 10cm×10cm samples of the highly breathable fabrics obtained in each embodiment and the comparative example, dry them at 100℃ for 2h, weigh them m0, let them stand at 25℃ and humidity 65% ​​for 30min, weigh them m1 again, and calculate the moisture content = m1-m0 / m0*100%.

[0030] Air permeability test method: The highly air permeable fabrics obtained in each embodiment and the comparative example were taken with the same size, and the air permeability was tested under a pressure of 100 Pa using a YG461E fully automatic air permeability instrument in accordance with GB / T5453.

[0031] 2. Long-lasting antibacterial properties Test method: Take 0.75g of the highly breathable fabric obtained in each embodiment and the comparative example, wash with deionized water for 5min, dry at 60℃ for 1h, repeat washing and drying 15 times, and put into 5mL of 4×10 9 coli liquid with a concentration of 0.03 mol / L and 70 mL of PBS buffer with a concentration of 0.03 mol / L were placed in a conical flask and shaken at 24°C and 150 r / min for 18 h on an air bath constant temperature shaker to obtain the test solution; 1 mL of the test solution was diluted with 0.03 mol / L PBS buffer by 10 2 times, spread the plate with a spreader, put it in a constant temperature incubator, culture it at 37℃ for 24h, and measure the viable bacteria concentration = colony count / 10 2 .

[0032] 3. Mechanical properties Test method: Take the same length of the highly breathable fiber obtained in each embodiment and the control example, and test the breaking strength σb0 according to GB / T14337 using a YG004E electronic single fiber strength tester at 25°C, 65% humidity, a tensile speed of 20mm / min, and a clamp distance of 25mm to determine the mechanical properties.

[0033] 4. Anti-light and oxygen aging performance Test method: The high air permeability fibers obtained in each embodiment and the comparative example were taken with the same length, and tested at a light source density of 25 W / m 2 After aging for 30 hours under the conditions of 300W power, 65% relative humidity and 65℃ test temperature, the breaking strength σb1 was measured again, and the strength retention rate = σb1 / σb0*100% was calculated to judge the anti-light and oxygen aging performance.

[0034] Table 1 below shows the analysis results of the moisture absorption and air permeability, long-lasting antibacterial properties, mechanical properties and anti-photooxidation aging properties of the highly breathable fabrics of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3.

[0035] Table 1

[0036] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the highly breathable fabric prepared by the present invention has good moisture absorption and breathability, long-lasting antibacterial properties, mechanical properties and resistance to light and oxygen aging.

[0037] By comparison, Examples 1 to 3 and Comparative Examples 1 to 3 all have good air permeability, which illustrates that using small molecular weight polyethylene glycol as a porogen to form a fine pore structure improves the air permeability of the highly breathable fabric.

[0038] By comparison, Examples 1, 2, and 3 have higher moisture content and breaking strength than Comparative Example 1 and lower live bacteria concentration, which indicates that allyl succinic anhydride is grafted onto cotton cellulose through esterification reaction, carbon-carbon double bonds and carboxyl groups are introduced, and carboxyl groups and amino groups are reacted to form hydrophilic amide bonds while introducing terpyridine structures, and silver ions are complexed to form a stable coordination structure, thereby improving the hygroscopicity and durable antibacterial properties of the highly breathable fabric; and then the carbon-carbon double bonds are reacted with hydrogen-containing silicone oil to form a cross-linked network, thereby improving the mechanical properties of the highly breathable fabric.

[0039] By comparison, Examples 1, 2, and 3 have higher moisture content, breaking strength, and strength retention rate than Comparative Example 2, which indicates that 2,4-diamino-6-vinyl-S-triazine and 2,6-di-tert-butyl-4-bromomethylphenol are grafted sequentially on graphene oxide, and the synergistic effect of the triazine ring and the hindered phenol structure is utilized to absorb ultraviolet rays while capturing oxidative free radicals, thereby improving the anti-aging properties of the highly breathable fabric; hydrophilic amide bonds are formed when 2,4-diamino-6-vinyl-S-triazine is grafted, thereby improving the hygroscopicity of the highly breathable fabric; the retained carbon-carbon double bonds participate in the hydrosilylation reaction to form a cross-linked network, thereby improving the mechanical properties of the highly breathable fabric.

[0040] By comparison, the live bacteria concentrations of Examples 1, 2, and 3 are lower than that of Comparative Example 3, which indicates that the addition of silver nitrate to the spinning solution can improve the durable antibacterial property of the highly breathable fabric by forming a stable coordination structure with terpyridine.

[0041] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A highly breathable fabric, characterized in that: The highly breathable fabric is obtained by mixing modified cellulose, modified graphene oxide, hydrogen-containing silicone oil, polyethylene glycol and silver nitrate and spinning and weaving them; The modified cellulose is obtained by sequentially reacting cotton cellulose with allyl succinic anhydride and 4'-amino-2,2':6',2''-terpyridine; The modified graphene oxide is obtained by reacting graphene oxide with thionyl chloride, 2,4-diamino-6-vinyl-S-triazine and 2,6-di-tert-butyl-4-bromomethylphenol in sequence.

2. A method for preparing a highly breathable fabric, characterized in that: The method comprises the following preparation steps: (1) Cotton cellulose, urea and choline chloride were mixed in a mass ratio of 1:(24-26):(24-26), stirred at 75-85°C and 200-300 rpm for 4-6 min, allyl succinic anhydride was added in an amount of 2-4 times the mass of cellulose, cooled to 55-65°C and stirred for 5-15 min, anhydrous ethanol was added in an amount of 13-15 times the mass of cellulose, allowed to stand until the mass of the precipitate did not increase, and then centrifuged, washed with anhydrous ethanol for 3-5 times, and dialyzed in deionized water for 71-10 min using a 900-1100 Da dialysis membrane. 73h, freeze-dried to obtain pre-modified cellulose; the pre-modified cellulose and deionized water were mixed at a mass ratio of 1:(900-1100), ultrasonically dispersed for 10-20min, 4'-amino-2,2':6',2''-terpyridine in an amount of 2-3 times the mass of the pre-modified cellulose was added, stirred at 55-65℃ and 350-450r / min for 3-5h, cooled naturally to room temperature and then centrifuged, washed with deionized water and anhydrous ethanol for 3-5 times respectively, dried at 65-75℃ for 8-10h to obtain modified cellulose; (2) Graphene oxide, thionyl chloride, N,N-dimethylformamide and anhydrous acetonitrile were mixed in a mass ratio of 1:(11-12):(0.9-1.1):(900-1100), stirred at 55-65°C and 100-200 rpm for 4-6 hours, and 2,4-diamino-6-vinyl-S-triazine (16-17 times the mass of graphene oxide) was added. The mixture was stirred for another 4-6 hours and then centrifuged. The mixture was washed with deionized water for 3-5 times and freeze-dried. , obtaining pre-modified graphene oxide; mixing the pre-modified graphene oxide, 2,6-di-tert-butyl-4-bromomethylphenol, triethylamine and dichloromethane in a mass ratio of 1:(2-3):(0.01-0.02):(13-14), stirring at -1-1°C and 200-300rpm for 55-65min, filtering, washing with ethyl acetate and deionized water for 3-5 times respectively, and drying at 55-65°C for 5-7h to obtain modified graphene oxide; (3) Modified cellulose, modified graphene oxide, hydrogenated silicone oil, polyethylene glycol, dichloromethane and dimethyl sulfoxide are mixed in a mass ratio of 1:(0.02-0.04):(0.4-0.6):(0.01-0.02):(2.2-2.3):(6.7-6.8), and stirred at 20-30°C and 100-200 rpm for 20-30 min. Chloroplatinic acid (0.01-0.02 times the mass of the modified cellulose) and silver nitrate (0.02-0.04 times the mass of the modified cellulose) are added, and stirring is continued for 5-15 min to obtain a spinning solution. The spinning solution is subjected to electrospinning. After spinning, the spinning solution is allowed to stand at 75-85°C for 10-12 h, washed with deionized water for 3-5 times, and dried at 60-70°C for 8-10 h to obtain a highly breathable fiber. The highly breathable fiber is spun and woven by a textile machine to obtain a highly breathable fabric.

3. The method for preparing a highly breathable fabric according to claim 2, characterized in that: The reaction equation of the pre-modified cellulose in step (1) is: 。 4. The method for preparing a highly breathable fabric according to claim 2, characterized in that: The reaction equation for the modified cellulose in step (1) is: 。 5. The method for preparing a highly breathable fabric according to claim 2, characterized in that: The reaction equation of the pre-modified graphene oxide in step (2) is: 。 6. The method for preparing a highly breathable fabric according to claim 2, characterized in that: The reaction equation for modifying graphene oxide in step (2) is: 。 7. The method for preparing a highly breathable fabric according to claim 2, characterized in that: The spinning conditions of the electrospinning in step (3) are: spinneret inner diameter 0.6 mm, spinning voltage 17 kV, receiving distance 17 cm, and injection pump flow rate 6.8 μL / min.

Citation Information

Cited By

  • Breathable anti-deformation polyester fiber fabric, preparation method thereof and application of breathable anti-deformation polyester fiber fabric in bags and suitcases

    CN119686122A

  • Adsorption filtering membrane for treating heavy metal ion pollution of water body and preparation method of adsorption filtering membrane

    CN119951355A